2014
DOI: 10.7314/apjcp.2014.15.22.10021
|View full text |Cite
|
Sign up to set email alerts
|

Age of Diagnosis of Breast Cancer in China: Almost 10 Years Earlier than in the United States and the European Union

Abstract: Background: The study aimed to describe the age distribution of breast cancer diagnosis among Chinese females for comparison with the United States and the European Union, and provide evidence for the screening target population in China. Materials and Methods: Median age was estimated from hospital databases from 7 tertiary hospitals in China. Population-based data in China, United States and European Union was extracted from the National Central Cancer Registry, SEER program and GLOBOCAN 2008, respectively. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
39
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(46 citation statements)
references
References 28 publications
7
39
0
Order By: Relevance
“…The age diagnosis of BC in China was 10 years earlier than that in USA, which was similar as that in a larger, national study reported recently [33]. Although in some developed areas of China like Shanghai, the age distribution of BC showed similar patterns of two peak ages because of similar lifestyle and longer life expectancy with Western countries, but the two peak ages (50e55 and 70e74 years) were still earlier than that in USA (60e64 and 80 years) [1e3,33].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The age diagnosis of BC in China was 10 years earlier than that in USA, which was similar as that in a larger, national study reported recently [33]. Although in some developed areas of China like Shanghai, the age distribution of BC showed similar patterns of two peak ages because of similar lifestyle and longer life expectancy with Western countries, but the two peak ages (50e55 and 70e74 years) were still earlier than that in USA (60e64 and 80 years) [1e3,33].…”
Section: Discussionsupporting
confidence: 87%
“…US had already initiated the national screening program for several decades. Unfortunately, although some screening programs for BC have been performed in local developed areas in China, the nationwide screening program has not been conducted [3,33]. Additionally, the lower ER positive rate indicated more patients with aggressive BC, which needs to earlier diagnosis and intensive treatment.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…It would be interesting that a similar study could be conducted among Caucasians: A same result would suggest a general phenomenon; a different result may be explained by the interaction between genes and environments [34]. It is also likely that menopausal status may be able to explain the phenomena to some extent, because European incident breast cancer patients are usually older (postmenopausal) than Chinese [35], while the association particularly occurred among postmenopausal women as found in previous studies [36,37] as well as in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…1 The age of development and diagnosis of breast cancer is much younger in China than in the United States and the European Union. 2 Mastectomy is associated with psychological trauma for many patients. 3 Surgical therapy for breast cancer has evolved from radical mastectomy to breast-conserving techniques.…”
Section: Introductionmentioning
confidence: 99%